(untitled) (IUPHAR/BPS Guide to Pharmacology CITE, 2025)
The 2TM domain family of K channels are also known as the inward-rectifier K channel family. This family includes the strong inward-rectifier K channels (Kir2.x) that are constitutively active, the G-protein-activated inward-rectifier K channels (Kir3.x) and the ATP-sensitive K channels (Kir6.x, which combine with sulphonylurea receptors (SUR1-3)). The pore-forming α subunits form tetramers, and heteromeric channels may be formed within subfamilies (e.g. Kir3.2 with Kir3.3).